2021
DOI: 10.1002/adom.202002031
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Detectivity in Spatially Separated Hole/Electron Dual Traps Based Near‐Infrared Organic Phototransistor

Abstract: In phototransistors, the photovoltaic‐induced current is proportional to the turn‐on voltage shift and the total number of trapped charges. However, it is challenging to obtain a high turn‐on voltage shift simply by using minority carrier trap sites because high‐concentration carrier trap sites introduce strong current traps and carrier recombination. In this study, spatially separated, hole/electron, dual traps are introduced into a phototransistor, demonstrating the possibility of combining hole and electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…[58,59] If the shot noise from the dark current is the major contributor to limit the detectivity, D * can be expressed as equation ( 3). [32] These key factors of the device under P ill of 3, 1.5, 0.3, 0.15, and 0.03 mW cm -2 and bias of V g = 0 V and V d = 100 V are exhibited in Table 1. By comparing these values, R and ∆V th , as a function of P ill , are plotted in Figure 6a,b, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[58,59] If the shot noise from the dark current is the major contributor to limit the detectivity, D * can be expressed as equation ( 3). [32] These key factors of the device under P ill of 3, 1.5, 0.3, 0.15, and 0.03 mW cm -2 and bias of V g = 0 V and V d = 100 V are exhibited in Table 1. By comparing these values, R and ∆V th , as a function of P ill , are plotted in Figure 6a,b, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Fullerene derivatives are dominantly selected as the electron acceptors, while many electron donors are available for photodetection layer assembling. [28][29][30][31][32][33][34][35][36][37] However, the fullerenes suffer from insufficient red light absorption, due to their wide Semiconducting blend heterostructures, composed of conjugated polymer with photoresponsive organic crystals, provide an effective way to achieve promising photodetection devices. Here, solution-processed n-type N2200 conjugated polymer and quinoidal thienoisoindigo (TIIQ) small molecule blend is used to construct phototransistors for red light detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the recently developed OPTs are based on the hybrid effect, i.e., depositing the organic absorbing layers on high-mobility metal oxides, e.g., ZnO or indium zinc oxide (IZO), , which are inorganic and not flexible. Another strategy is to blend the photosensitive materials within the charge transport channels and form the hybrid layers, which combine charge generation and charge transfer somehow. For instance, the channels based on BHJs do enhance exciton separation and charge transport, but the conductivity of the channel increased significantly under illumination, which also diminishes the transfer curves of the OPTs severely; that is, the transistors cannot be fully “switched off” by adjusting the gate voltage.…”
Section: Introductionmentioning
confidence: 99%
“…10 Our group has achieved organic phototransistor (OPT) with an ultrahigh response (R > 5.7 × 10 3 A W −1 and G > 1.8 × 10 4 ) in a wide wavelength range (410−740 nm) 11 and a NIR-OPT response showing an ultrahigh detectivity of 1.88 × 10 15 jones at 820 nm. 12,13 Limbu et al have identified the impact of molecular structural properties on the blend energetics and optoelectronic properties. They believed that strong molecular coupling between donor and acceptor molecules in highly intermixed all-small molecule bulk heterojunction blends determines the optoelectronic properties of OPD devices.…”
Section: Introductionmentioning
confidence: 99%